Implementation of Financial Management Patterns (BLUD): Analysis of Obstacles and Performance Improvement Strategies (Literature Study) - I Gusti Agung Kumala Dewi; I Ketut Suarjana (Indonesian Journal of Global Health Research, 2026)
The implementation of the Regional Public Service Agency (BLUD) Financial Management System in Community Health Centers (Puskesmas) is one of the government's efforts to improve the efficiency of financial management and the quality of health services to the public. The BLUD system provides flexibility for health service units to manage financial resources more effectively and accountably. This study aims to analyze the implementation of BLUD financial management in Community Health Centers and identify various factors influencing its successful implementation. This study used a literature review approach by analyzing national and international scientific articles relevant to BLUD implementation in primary health care facilities. Data collection was conducted through a search of scientific databases and analyzed descriptively thematically. The study shows that BLUD implementation has a positive impact on financial management flexibility, operational efficiency, and improved health service quality. However, several obstacles are still frequently encountered, including limited regulatory support at the regional level. Increasing human resource capacity, strengthening organizational governance, and policy support from the regional government are important factors in supporting the successful implementation of BLUD in Community Health Centers.